Discrimination in a Rank Order Contest. Evidence from the NFL Draft - Ian Gregory-Smith; Alex Bryson; Rafael Gomez (Institute of Labor Economics (IZA), 2022)
This paper examines discrimination in the NFL draft. The NFL is a favourable empirical setting to examine the role of skin colour because franchise selectors are required to make rank-order judgements of players based on noisy signals of future productivity. Since wages are tightly related to the rank-order of the draft for the first four years of a player's career, even if discrimination plays only a marginal role in selection, there could be a large discriminatory impact. We observe large unadjusted racial differences in drafting. However, much of the variation is explained by Black and White players selecting into different playing positions. Conditional upon a large set of control variables, including athletic performance at a marque selection event (the NFL combine), we do not find robust evidence of racial discrimination in NFL drafting between 2000 and 2018.
Keywords: J15; J24; 330; discrimination; race; NFL